Kako zgodoviniti slovensko sodobno gledališče? - Toporišič, Tomaž (Amfiteater (Ljubljana), 2017)
The essay deals with the question of how to historicise the innovative theatre of the Slovenian neo-avant-garde group Pekarna. The starting point is the book of Ivo Svetina The Pekarna Theatre (1971-1978). The Birth of Theatre from the Spirit of Freedom: Testimony (Gledališče Pekarna (1971-1978). Rojstvo gledališča iz duha svobode: pričevanje), which marks a first attempt to give an outline and insight into this theatrical phenomena of the contemporary Slovenian theatre in the second half of the twentieth century. It concludes that Svetina's book historicises the phenomenon with a precise, engaging, original approach and a specific openness of the essayistic form enabling a new insight into the body of the performative turn of Slovenian drama and theatre in the 1970s. The book shows how the contemporary art in the time of socialism had to struggle for its very existence. Because of the marginal position of the Slovenian experimental theatre, already in the 1980s the history of the theatre had nearly forgotten the fundamental shifts of the Pekarna Theatre, the Glej Theatre and the Pupilija group. Thus these important artistic phenomena that changed the history of Slovenian theatre had to be reinterpreted and rediscovered much later: after the turn of the century and millennium. In its attempt to historicise the neo-avant-garde, Svetina's book discloses the thus far often hidden or blurred histories of art, produced and also theoretically manifested by the post-dramatic performative group Pekarna as well as some other experimental initiatives in Slovenia, which occurred in the specific political, cultural and intellectual space of the self-managing socialist Slovenia and Yugoslavia of the 1970s, between East and West, North and South.
Keywords: 1971/1978; 20.st.; eksperimentalno gledališče; Ljubljana; ocene in poročila; slovensko gledališče; Svetina, Ivo: Gledališče Pekarna